MANAJEMEN PENGELOLAAN TERPADU SAMPAH PERKOTAAN STUDI KASUS: KOTA KENDARI - Dwi Rinnarsuri Noraduola (Metropilar - Jurnal Ilmiah Fakultas Teknik, 2008)
Urbanization, accompanied by the increase of population and living of standard, causes the increase of consumption, both product and service, which is concentrated in urban area. Waste as residual material of that consumption has to be handled properly, respectively to the fact that solid waste management is an essential element of public health, environment and aesthetic quality of urban area. Unfortunately, in the case of Kendari Municipality, there is unbalance between waste generation and the capacity of solid waste management of Municipality, which shows the inefficiency of implemented management. The lack of implementation of alternative method of solid waste management; capacity building in term of human resource; financial source and public awareness are identified as the factors influencing that inefficiency. Respectively to the identified factors, the implementation of integrated solid waste management in Kendari Municipality is urgently needed. Key words: Integrated solid waste management; alternative method; capacity building; financial source and public awareness.